[Memo from Pete Sparber to Sam Chilcote regarding Tobacco Workers Advertising Campaign] - PETE SPARBER (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Memo from Pete Sparber to Sam Chilcote regarding "I'm the tobacco industry, too" advertising campaign attached to draft of advertisement. Discusses strategy of placing ads in liberal magazines and asking liberals to think before they attack the tobacco industry. Encourages contributing to funding for advertising campaign.